Mathematics tutoring from the perspective of lower secondary pupils - Novotná, Gabriela (e-Pedagogium, 2022)
Popularity of tutoring has recently been increasing, however, in the Czech Republic tutoring has not been strongly theoretically anchored yet. A quantitative study was conducted among 318 lower-secondary pupils in Prague. It was ascertained that 86% of the respondents have personal experience with tutoring, roughly one third of them have participated in tutoring of mathematics. Their participation in tutoring led by a majority to positive changes, such as better school grades and better understanding of a subject matter. Some situations would be liked to be seen more often when tutoring compared to schooling, mainly solving tasks in various connections and learning based on own mistakes. It was shown that interest in math tutoring increases among pupils (not only due to pupil' positive beliefs), which also influences the schooling, and that pupils would appreciate a higher individualisation of their education and broadening their knowledge during their tutoring.
Keywords: tutoring; mathematics; pupils' notions.